Selp: A Single-Shot Epistemic Logic Program Solver. Issue 4 (26th July 2020) - BICHLER, MANUEL; MORAK, MICHAEL; WOLTRAN, STEFAN
Abstract: Epistemic logic programs (ELPs) are an extension of answer set programming (ASP) with epistemic operators that allow for a form of meta-reasoning, that is, reasoning over multiple possible worlds. Existing ELP solving approaches generally rely on making multiple calls to an ASP solver in order to evaluate the ELP. However, in this paper, we show that there also exists a direct translation from ELPs into non-ground ASP with bounded arity. The resulting ASP program can thus be solved in a single shot. We then implement this encoding method, using recently proposed techniques to handle large, non-ground ASP rules, into the prototype ELP solving system "selp, " which we present in this paper. This solver exhibits competitive performance on a set of ELP benchmark instances.